Hybrid Education and Digital Pedagogy: The Role of Technological Platforms and Artificial Intelligence in Enhancing Educational Processes - Pusca, Corneliu Andy (Didactica Danubiensis, 2024)
The integration of hybrid education and digital pedagogy has significantly transformed the educational landscape, offering a blend of traditional and modern teaching methods. This paper examines the impact of advanced technologies such as artificial intelligence (AI), virtual reality (VR), and digital platforms on enhancing learning experiences. Using a mixed-methods approach, we analyze qualitative interviews with educators and quantitative surveys among students to assess the effectiveness of these tools in improving engagement, personalization, and overall academic performance. The findings underscore the need for continuous professional development for educators and highlight ethical considerations, including data privacy and the digital divide.